2018
DOI: 10.1111/echo.14139
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mitral annular velocities after cardioversion of atrial fibrillation

Abstract: We demonstrated that e' was significantly higher in AF compared with during sinus rhythm in the same patients. Thus, in AF patients, diastolic dysfunction should be suspected even when e' values are normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In our study, septal, lateral, and average e' decreased, whereas E/e' increased, but the change remained statistically insignificant. This result is similar to the findings of Park et al, 12 where e' was significantly higher in AF compared with during SR in the same patients. Restoration of atrial mechanical contraction following ECV improved LV systolic function, assessed by s', and together had a larger impact on LV function assessed by E/(e'xs') ratio that statistically significantly improved.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, septal, lateral, and average e' decreased, whereas E/e' increased, but the change remained statistically insignificant. This result is similar to the findings of Park et al, 12 where e' was significantly higher in AF compared with during SR in the same patients. Restoration of atrial mechanical contraction following ECV improved LV systolic function, assessed by s', and together had a larger impact on LV function assessed by E/(e'xs') ratio that statistically significantly improved.…”
Section: Discussionsupporting
confidence: 92%
“…[5][6][7][8][9][10] A comprehensive systematic review by D. Kotecha reported that diastolic function indices, particularly E/e', are valid and reproducible in patients with AF when the appropriate cardiac cycles are carefully selected. 11 Nevertheless, Park et al 12 revealed in their small study that E/e′ was significantly lower in AF compared with SR during 1 month after ECV in the same patients. There is limited data demonstrating how e' changes after SR restoration in AF patients and this information is useful to confirm E/e' ratio constancy in AF patients.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Park et al. reported that the e' values during AF were significantly higher than that during sinus rhythm in the same patients receiving electrical cardioversion to restore sinus rhythm 23 . Thus, the E/e' values during AF were expected to be inappropriately lower than that during sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, some patients received transthoracic echocardiography during AF. procedure could cause unreliable results for estimating the LVDD in AF patients.Park et al reported that the e' values during AF were significantly higher than that during sinus rhythm in the same patients receiving electrical cardioversion to restore sinus rhythm 23. Thus, the E/e' values during AF were expected to be inappropriately lower than that during sinus rhythm.…”
mentioning
confidence: 99%